Self-organizing map applied to the choice of internal standards for the determination of Cd, Pb, Sn, and platinum group elements by inductively coupled plasma mass spectrometry - Moreira, Luana S.; Costa, Floriatan S.; Machado, Raquel C.; Nogueira, Ana Rita A.; Gonzalez, Mario H. [UNESP]; da Silva, Erik G.P.; Amaral, Clarice D.B. (Elsevier, 2021)
The behaviors of internal standards, according to different flow rates of the cell collision gas (He), were studied for the determination of Cd, Pb, Pd, Pt, Rh, and Sn in samples of fish and mollusks by inductively coupled plasma mass spectrometry (ICP-MS). The elements Bi, Ge, In, Sc, and Y were selected as internal standards, considering their masses and first ionization energies. Addition and recovery experiments were carried out at three concentration levels to evaluate the accuracy of the method applied for the analysis of two samples with different matrices. The results were evaluated using a self-organizing map (SOM). The best analyte/IS pairs were as follows: 114Cd+/74Ge+, 195Pt+/74Ge+, and 208Pb+/74Ge+. For 103Rh+, 106Pd+, and 120Sn+, greater accuracy was achieved without use of an internal standard. Helium gas (2.8 mL min−1) was used in the collision cell for the analytes, except for Sn, and recoveries ranged from 98 to 101% under optimal conditions. The use of SOM as an exploratory analysis tool was an effective approach for selection of the most appropriate internal standards.
Keywords: Bivalve mollusks; Fish; ICP-MS; PGEs; Self-organizing map; Toxic elements